Incidental L2 vocabulary learning from viewing captioned videos: Effects of learner-related factors. (April 2022) - Teng, Mark Feng
Abstract: Studies using captioned videos have shown benefits for incidental vocabulary learning. However, little research has considered learner-related factors in this type of learning by viewing captioned videos. The present study aims to fill this gap by examining the impact of watching a documentary TV program on incidental vocabulary learning and assessing to what extent this learning is influenced by learner-related factors (i.e., L2 proficiency level and language aptitude). Eighty-two Chinese-speaking EFL learners were divided into two groups: one that watched a video with captions and another that watched a video without captions. Measures included four dimensions of vocabulary knowledge (i.e., recognition and recall of word form and meaning); L2 proficiency level and language aptitude were controlled as covariates. MANCOVA results demonstrated that viewing a documentary video affected incidental vocabulary learning to varying degrees in terms of recognizing and recalling word form and meaning. The caption group made considerably more significant vocabulary learning gains than the group not exposed to captions. The examined learner-related variables also significantly influenced incidental vocabulary learning gains when viewing captioned videos. However, L2 proficiency level was not a significant predictor of word meaning recall and recognition. These findings provide pedagogical implications for using captioned videos to enhance incidental vocabulary learning.